Misreading the Bengal Delta : climate change, development, and livelihoods in coastal Bangladesh - Dewan, Camelia (University Press Limited, 2023)
"Key global players increasingly politicize discussion of climatic change. This is especially evident in regard to Bangladesh, much of which is perilously close to sea level and vulnerable to flooding, and which has long been the recipient of various development schemes for "poverty reduction" or "progress" to justify interventions in its environment and society. Some of these projects have resulted in severe, often unintended, environmental effects, such as silting of waterbodies that are surrounded by embankments; biodiversity loss and weakening of the sea walls (which protect against floods) resulting from tiger-prawn monoculture; and loss of soil fertility in intensive agriculture. Camelia Dewan utilizes ethnography and environmental history to highlight flawed assumptions of international development projects in Bangladesh, which often misread the coastal landscape by attributing causality solely to climate change. Examination of multiple and often conflicting perspectives-from poor rural coastal populations, middle-class elites, political actors, and NGO staff-shows how, since the colonial era, Bangladesh has endured intrusions, and how its current environmental crisis goes beyond global warming. This case study informs broader issues worldwide by documenting how the idea of climate change shapes development projects in the Global South, and the extent to which these endeavors correspond with the problems and concerns of populations they are intended to help. This provocative study will be welcomed by readers in the fields of environmental anthropology, human geography, and development studies"--